An 18-Year Overview of Serratia marcescens Ocular Infection. Issue 8 (August 2021) - Atta, Sarah; Perera, Chandrashan; Nayyar, Shannon; Kowalski, Regis P.; Jhanji, Vishal
Abstract : Purpose: Serratia marcescens is a frequent ocular bacterial pathogen implicated in keratitis, endophthalmitis, and conjunctivitis. We evaluated the risk factors and treatment outcomes of ocular infections due to S. marcescens . Methods: In this retrospective observational study, all S. marcescens -positive cases between February 2002 and February 2020 were reviewed for ocular risk factors that included log of minimal angle of resolution visual acuity (VA), medical management, and time to epithelial defect closure. Results: Fifty-one patients were identified (72.5% females, 46.8±23.3 years). Forty-six patients had complete medical records, and 5 had microbiology data available. The most prevalent ocular risk factors were, contact lens (CL) use (68.6%), corneal disease (52.9%), and history of ocular surgery (41.2%). Mean presenting VA was 1.3±1.0. About half of the patients presented with a central ulcer (49%, 25), large infiltrate (20.4±31.8 mm 2 mean), and hypopyon (43.1%, 22). All cases were reported to be susceptible to ciprofloxacin. Defect closure occurred in 52.3±117.1 days and final VA was 0.86±0.88. Adjunctive treatments were required in 14 cases (27.5%). One patient underwent surgical intervention. Features associated with poor VA outcomes included, history of glaucoma ( P =0.038), older age at presentation ( P <0.001), presence of hypopyon (0.045), poor VA at presentation (0.0086), time to epithelial defect closure (0.0196), and large infiltrate size ( P =0.0345). Conclusions: S. marcescens keratitis and conjunctivitis is associated with CL use and history of ocular surface disease. Worse outcomes were associated with older age, infiltrate size, presence of hypopyon, worse initial VA, longer time to epithelial defect closure, and history of glaucoma.